Sheehan’s Syndrome Revisited: Underlying Autoimmunity or Hypoperfusion? - González González, José Gerardo; Borjas Almaguer, Omar David; Salcido Montenegro, Alejandro; Rodríguez Guajardo, René; Elizondo Plazas, Anasofia; Montes de Oca Luna, Roberto; Rodríguez Gutiérrez, René (2018)
Sheehan’s syndrome remains a frequent obstetric complication with an uncertain pathophysiology. We aimed to assess the incidence of hypopituitarism (≥2 hormonal axis impairment) within the ﬁrst six postchildbirth months and to determine the existence of anti-pituitary antibodies. From 2015 to 2017, adult pregnant women, who developed moderate to severe postpartum hemorrhage (PPH), were consecutively included in the study. Pituitary function was assessed 4 and 24 weeks after PPH. At the end of the study, anti-pituitary antibodies were assessed. Twenty women completed the study. Mean age was 26.35 (±5.83) years. The main etiology for severe PPH was uterine atony (65%) which resulted mostly in hypovolemic shock grades III-IV. Within the ﬁrst four weeks after delivery, 95% of patients had at least one hormonal pituitary aﬀected and 60% of the patients fulﬁlled diagnostic criteria for hypopituitarism. At the end of the study period, ﬁve patients (25%) were diagnosed with hypopituitarism (GH and cortisol axes aﬀected). Anti-pituitary antibodies were negative in all patients. At 6 months follow-up, one in every four women with a history of moderate-to-severe PPH was found with asymptomatic nonautoimmune-mediated hypopituitarism. The role of autoimmunity in Sheehan’s syndrome remains uncertain. Further studies are needed to improve the remaining knowledge gaps.